PERBEDAAN PERTUMBUHAN BAYI BARU LAHIR PADA METODE LOTUS BIRTH - Herlyssa Herlyssa; Sri Mulyati; Rus Martini (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Newborns health,which is measured by the growth of body in weight and length after born,is determined by maternal and nenatal factors, particularly the time to pinch or cut placentacord..This study aims to examine the relationship betweendelivery method with leaving theplacenta uncut(lotus birth) andthe growth of newborn. This is designed as crosessectionalresearch, with the use of secondary data from medical record at two maternity clinics inEast Jakarta. The research population is mothersthosegivevaginal birth at the Clinics. Thesampling technique used the total number of population member, namely 111 respondents.This research results in 63,1% of total sample attended lotus birth with their baby's weightat birth is 3085 gramon average. Oneweek and one month later, the weight increases to3431, and 4542,34gram on average respectively. Statistical test analysis T testshows thatthe growth of 1 week newborns under lotus birth methode is better than those who useordinary birth with significant P value is 0.00. Thus, delaying umbilical cord cut at birthat lotus birth methode requires further verification.